IMPROVING SERVICE DELIVERY BY INSPECTORS OF THE DEPARTMENT - Madzivhe, Nnditsheni Thomas (My University, 2011)
With the advent of new democracy in South Africa during 1994, the Department of Labour was faced with challenges of ensuring compliance with labour laws aimed at improving working conditions, create health and safe working environment and to ensure worker access to both unemployment and compensation benefits. The purpose of the survey research was to understand the service delivery model of inspection and enforcement services, with key focus on inspectors, in order to facilitate service delivery improvements. One of the key findings of the research was thou the conception of the one stop service (integrated inspection) model was good, there are key implementation challenges that requires attention. Another finding was of those inspectors who had tertiary qualifications, the qualifications were mostly non-technical. Professionalisation of inspectors work is one way of improving service delivery’.(
MM - P&DM
Keywords: Service delivery; Department of Labour